Contingency and Faithfulness: Francis Alÿs and the (Re)Presentation of St. Fabiola - Anderson, Jonathan A. (Religion and the arts, 2014)
‭As a European emigrant to (and now longtime resident of) Mexico City, contemporary artist Francis Alÿs is deeply sensitive to the ways that cultural systems shape and organize human lives. Over two decades, his work has become deftly efficient at instigating subtle social interferences that highlight and reconsider these organizing systems. Although much has been written about the social and political force of these interferences, the literature on Alÿs’s work has generally ignored the significant religious content and allusions recurring throughout his artistic practice. This essay is a critical meditation on the religious implications of his Fabiola project, a collection of more than 370 handmade copies of a lost nineteenth-century painting of a fourth-century Christian saint named Fabiola. By paying special attention to the ways that these “handmade readymades” ennoble the voices of others and revise the possible meanings of visual repetition (particularly in the context of mechanical mass-reproduction), this essay argues that Alÿs’s Fabiola is not only a profound study of cultural transmission but one that is particularly resonant with the Christianity that formed St. Fabiola’s own life and the forms by which she has been remembered.‬